THE STUDY PHARMACOKINETIK CODEINE IN RABITT AFTER INTRAVENUS BOLUS - Wirasuta, I Made Agus Gelgel; Listiari, Ni Made; Swastini, Dewa Ayu (Buletin Veteriner Udayana, 2019)
The codeine has been used as a marker for illicit heroin uses, that for increasing differentiating illicit heroin uses, it needs the codeine pharmacokinetic data. Eleven rabbits have been injected 11.04 mg codeine (with body weight: ± 1.8 kg) via marginal vena . Blood has taken at every 5, 15, 30, 60, 90, and 120 minutes. Serum has stored at -20 0 C before analyzed. Blood protein was predicated by isoprophanol. Codeine was extracted with chloroform-isopropanol (3:1) and buffer phosphate 0.2N pH 9.3 then separated by phase toluene-acetone-ethanol-ammonia (45:45:7:3) as mobile phase and aluminium sheet of silica thin layer chromatography Gel 60 F 254 as the stationary phase. Codeine determined by spectrophotodensitometry at 215 nm. Limit of detection and limit of quantification of codeine was 184.43 ng and 563.62 ng per spot, respectively the percentage recovery of in vitro was 60.60%. Profile concentration of codeine after IV bolus showed decreasing concentration at the first terminal and increasing codeine concentration at the last terminal that indicated an enterohepatic cycle. Codeine pharmacokinetic followed the first compartment with the half time was 30.61 minutes and the distribution volume was 7760.50 mL. Enterohepatic cycle caused a prolonged lifetime of codeine at the rabbit